Microbial Wonders: Significant Role in Solid Waste Management - Meena, S; Manimekalan, A.; Radhakrishnan T. (Emerging Issues in Environment, Geography and Earth Science Vol. 7, 2024)
The primary objective of this study is to convert the biodegradable solid waste into lactic acid, a precursor of Poly lactic acid- PLA used as bioplastic. Urbanization and population growth have led to an increase in the generation of municipal solid waste (MSW) worldwide. Lactic acid bacteria (LAB) are used widely in food microbiology as probiotics and bio preservatives to extend the shelf life of food items. Lactic acid produced by LAB strains are precursor of polylactic acid (PLA) that has growing demand as bioplastics that are biodegradable in nature replacing traditional plastics. Important chemical parameters of the solid waste like phosphate estimation, nitrate estimation, Total organic carbon estimation were done following Indian standard analytical methods. Glucose consumption efficiency of Lacto bacillus sp.in the solid waste substrate was analyzed. Estimation of lactic acid produced was done in UV spectrometric analysis at 390nm using iron lactate formation. In this study, lactic acid bacteria were isolated from samples of milk, curd, idli batter and screened for lactic acid production. Solid waste collected was pretreated with dilute acid heating and hydrolysate obtained was used as substrate for lactic acid production under optimized parameters. Three isolates of Lacto bacillus sp. were good producers of lactic acid and utilized biodegradable solid waste in an effective manner. 3-5 gm/lit of lactic acid was produced by the three strains of Lacto bacillus sp. Segregation of domestic solid waste collected, comprised of 40% biodegradable fragment, 40% nondegradable plastic, 20% miscellaneous waste. Lactic acid production from biodegradable portion is a preliminary step experimented in this study progressing in polylactic acid PLA pathway indirectly reducing plastic pollution. In a similar manner, nonbiodegradable plastic waste can be minimized using Exopolysaccharide pathway by Xanthomonas sp. that is reviewed in this study. Disposal of solid waste in an economical and greener way is a smart method of saving environment. Bioconversion of plastic into pseudoplastic xanthan gum by Xanthomonas sp. (through exopolysaccharide pathway) are greener techniques to crush down the accumulated plastic mountains to ground level. Production of lactic acid, precursor of PLA from solid waste is a sustainable &greener method to dispose waste. Bioconversion of plastic into pseudo plastic-xanthan gum is a promising tool to minimize plastic pollution.